The Effect of Supply Chain Management on MSME Performance: The Mediating Influence of Human Resource Management Practices - Johanis R. Wanma; Fanny Kristin Tantyah Sitompul; Yasir Attamimi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
In an increasingly competitive and dynamic business environment, MSMEs must strengthen both operational efficiency and human resource capabilities to sustain and improve their performance. This study aims to analyze the effect of Supply Chain Management (SCM) on the performance of MSMEs by examining the mediating role of Human Resource Management Practices (HRMP). The research employed a quantitative approach using a survey of 113 MSME owners. Data were analyzed using Structural Equation Modeling with Partial Least Squares (Smart PLS) version 4.0.1. The results reveal that SCM has a positive and significant effect on both MSME performance and HRMP. Likewise, HRMP also positively and significantly affects MSME performance. These findings indicate that effective SCM implementation, including efficient procurement, inventory management, and distribution, enhances business performance when supported by effective HR practices such as training, compensation systems, and internal communication. However, HRMP does not significantly mediate the relationship between SCM and MSME performance. Therefore, MSME performance improvement is more strongly driven by direct SCM implementation rather than through HRMP mediation, implying that better integration between supply chain strategies and human resource management is essential to achieve optimal performance.